From Dependence to Autonomy
XIV, 278 p.
Keywords: This book is an example of an international editorial enterprise. The two editors, located in the United States and Singapore, coordinated a team of authors in ten countries. Linked by common concerns, the lengthy process of preparing such a complex volume proved to be a pleasantly cooperative task - proof that there is a kind of invisible college of colleagues working on similar topics in different countries. This book is also an indication that scholars from the Third World and the industrialized nations can work together in a spirit of equality and understanding. This project has an interesting origin. It was first discussed at a conference on ASEAN - American higher education held in Malaysia in 1985, sponsored by the Regional Institute for Higher Education and Development, then headed by V. Selvaratnam and funded by the Asia Foundation and the Lee Foundation. At the time, geographical coverage was to be limited to the ASEAN nations. We also sought external funding, without success, to assist us in developing the project. Due to lack of funding, the project languished for a year. When one of our original participants, Andrew Gonzales of the Philippines, produced an essay, we decided to proceed without funding. We also decided to add several additional key Asian nations that we felt would provide additional analytic scope to the book. The result of this somewhat unusual collaborative effort is this volume.